Estimating the Personal Distribution of Income with Adjustment for within- Family Variation - Lazear, Edward P.; Michael, Robert T. (Journal of Labor Economics, 1986)
The 1970 and 1979 Current Population Surveys are used to compute the personal distribution of income. The major innovation in this paper is that all individuals in the household are not treated identically. In particular, children receive a different proportion of income than do adults. That proportion is estimated. Its variations with respect to household characteristics are discussed, and a final distribution of personal income is computed. That distribution has considerably fatter tails than does the one normally used.